2015
DOI: 10.1007/s11307-015-0880-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Impact of Plasma Clearance and Down-regulation on GLP-1 Receptor Molecular Imaging

Abstract: Purpose Quantitative molecular imaging of beta cell mass (BCM) would enable early detection and treatment monitoring of type-1 diabetes. The glucagon like peptide-1 (GLP-1) receptor is an attractive target due to its beta cell specificity and cell surface location. We quantitatively investigated the impact of plasma clearance and receptor internalization on targeting efficiency in healthy B6 mice. Procedures Four exenatide-based probes were synthesized that varied in molecular weight, binding affinity, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 81 publications
5
26
0
Order By: Relevance
“…6,18,19,29 Whole organ fluorescence scans suffer from depth of imaging artifacts and provide arbitrary values (requiring the digest and dilution for absolute quantification) but agree qualitatively with the organ digest results (Figure S8). Previous studies have compared 800CW to radiolabels and have found antibody disposition is not significantly altered at sufficiently low DoL.…”
Section: Resultssupporting
confidence: 58%
“…6,18,19,29 Whole organ fluorescence scans suffer from depth of imaging artifacts and provide arbitrary values (requiring the digest and dilution for absolute quantification) but agree qualitatively with the organ digest results (Figure S8). Previous studies have compared 800CW to radiolabels and have found antibody disposition is not significantly altered at sufficiently low DoL.…”
Section: Resultssupporting
confidence: 58%
“…The biodistribution protocol was adapted from previously published protocols(41, 42). Briefly, after the animals were euthanized, organs were resected, weighed, and homogenized.…”
Section: Methodsmentioning
confidence: 99%
“…Careful consideration was taken when choosing dyes, as dye structure and molecular charge can greatly impact non-specific cellular and plasma protein interactions 49, 50 . Cy7 and Alexa Fluor 680 were chosen based on plasma protein binding of the free dye as determined by rapid equilibrium dialysis as well as previously published data on Cy7 exendin and s -AF680 exendin 32, 51 . All fluorescent peptides were purified with moderate yield (40–60%) and the exact mass confirmed by ESI-MS (SI).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to previously published work, either one or two AHA substitutions were made to generate single-mutant and double-mutant exendin 32, 51 . A methionine residue at the 14 th position was substituted with AHA during solid phase peptide synthesis based on its position pointing away from the binding pocket of GLP-1R 48 .…”
Section: Methodsmentioning
confidence: 97%